Autonomous service robot for human-aware restock, straightening and disposal tasks in retail automation. (17th September 2022) - Garcia Ricardez, Gustavo A.; Uriguen Eljuri, Pedro M.; Kamemura, Yuta; Yokota, Shiori; Kugou, Noriyuki; Asama, Yoshitatsu; Wang, Ziyu; Kumamoto, Hikaru; Yoshimoto, Kotaro; Chan, Wai Y.; Nagatani, Tomoki; Tulathum, Pattaraporn; et al.
Abstract : The workforce shortage in the service industry, recently highlighted by the pandemic, has increased the need for automation. We propose an autonomous robot to fulfill this purpose. Our mobile manipulator includes an extendable and compliant end effector design, as well as a custom-made automated shelf, and it is capable of manipulating food products such as lunch boxes, while traversing narrow spaces and reacting to human interventions. We benchmarked the solution in the international robotics competition Future Convenience Store Challenge (FCSC) where we obtained the first place in the 2020 edition, as well as in a laboratory setting, both situated in a convenience store scenario. We reported the results evaluated in terms of the score of the FCSC 2020 and further discussed the real-world applicability of the current system and open challenges. GRAPHICAL ABSTRACT: UF0001